Acotiamide improves stress‐induced impaired gastric accommodation. Issue 4 (14th November 2016) - Ikeo, K.; Oshima, T.; Sei, H.; Kondo, T.; Fukui, H.; Watari, J.; Miwa, H.
Abstract: Background: Gastric accommodation is a reflex reaction related to gastric reservoir function. Psychological stress, such as anxiety, inhibits gastric accommodation in humans. Acotiamide enhances the effect of acetylcholine in the enteric nervous system, enhances gastric contractility, and accelerates delayed gastric emptying. However, the effect of acotiamide on stress‐induced impaired gastric accommodation remains unclear. Therefore, we examined the effect of acotiamide on gastric accommodation and stress‐induced impaired gastric accommodation using a conscious guinea pig model. Methods: A polyethylene bag was inserted through the distal region of the gastric body into the proximal stomach of 5‐week‐old male Hartley guinea pigs. Gastric accommodation was evaluated by measuring the intrabag pressure in the proximal stomach after oral administration of a liquid meal. In the stress model, animals were subjected to water‐avoidance stress. Acotiamide (Z‐338) or nizatidine was administered subcutaneously. Fecal output was determined as the number of fecal pellets. Key Results: Administration of the liquid meal significantly decreased intrabag pressure, indicating induction of gastric accommodation. Acotiamide treatment prolonged liquid meal‐induced gastric accommodation and significantly increased the number of fecal pellets compared to controls. Water‐avoidance stress significantly inhibited liquid meal‐induced gastric accommodation. Pretreatment with acotiamide significantly improved stress‐induced impaired gastric accommodation. The number of fecal pellets in the acotiamide group increased significantly compared to controls. Acotiamide, but not nizatidine, significantly decreased gastric emptying. Conclusions & Inferences: Acotiamide prolongs gastric accommodation and improves stress‐induced impaired gastric accommodation, indicating a potential role for acotiamide in the treatment of functional dyspepsia through its effects on gastric accommodation reactions. Abstract : Pretreatment with acotiamide significantly improved stress‐induced impaired gastric accommodation. Acotiamide prolongs gastric accommodation and improves stress‐induced impaired gastric accommodation.